2015
DOI: 10.1007/s10856-014-5330-1
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of platinum nanoparticles that induce cell death and G2/M-phase cell cycle arrest in human cervical cancer cells

Abstract: Platinum-based chemotherapeutic drugs, including cisplatin, carboplatin, and oxaliplatin, have been used to manage cancer in spite of dose-dependent side effects, including nephrotoxicity, neurotoxicity and ototoxicity. These disadvantages have prompted the development of new strategies for cancer therapy that utilize functionalized nanoparticles as nanomedicines. In the present investigation, we have synthesized platinum nanoparticles using tea polyphenol (TPP) as both a reducing and surface modifying agent. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(44 citation statements)
references
References 54 publications
3
41
0
Order By: Relevance
“…catechins, theaflavins and thearubigins and their experimentation with Au 3? cations confirmed the involvement of these biomolecules in the GS of Au nanoparticles [46,64]. Similarly, isolation and purification of the tetra-nortriterpenoid azadirachtin has confirmed the reducing and capping role of Azadirachta indica in the GS of Au and Ag nanoparticles [45].…”
Section: Angiospermsmentioning
confidence: 58%
See 1 more Smart Citation
“…catechins, theaflavins and thearubigins and their experimentation with Au 3? cations confirmed the involvement of these biomolecules in the GS of Au nanoparticles [46,64]. Similarly, isolation and purification of the tetra-nortriterpenoid azadirachtin has confirmed the reducing and capping role of Azadirachta indica in the GS of Au and Ag nanoparticles [45].…”
Section: Angiospermsmentioning
confidence: 58%
“…Similarly, isolation and purification of the tetra-nortriterpenoid azadirachtin has confirmed the reducing and capping role of Azadirachta indica in the GS of Au and Ag nanoparticles [45]. Commercially available pure tea polyphenol (from Sigma) has been applied for the green synthesis of Pt nanoparticles [64]. These findings can be a very good platform in designing experiments for GS at large scale.…”
Section: Angiospermsmentioning
confidence: 73%
“…The extensive use of nanomaterials in several products, including electronics, cosmetics, textiles, medicines, paints, packaging and food materials, has raised health and environmental safety concerns for regulatory authorities Alshatwi et al, 2015;Stark et al, 2015;Rao et al, 2006;Chaudhry et al, 2008). Nanotoxicologists are beginning to evaluate the potential risks of engineered nanoparticles on health and the environment to overcome the insufficient toxicological information and current regulatory regimes in an effort to ensure the safe development and use of nanomaterials in commercial products (Aitken et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Because of their unique physical, chemical and biological properties, nanomaterials are causing a revolution in various enterprises, including electrical engineering, information technology and the food, medical and textile industries Alshatwi et al, 2015;Stark et al, 2015;Rao et al, 2006;Chaudhry et al, 2008). As a result, the occupational and public exposure to nanomaterials is increasing gradually year by year.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies have reported that G 2 /M phase arrest is negatively correlated with cell radiosensitivity, with significant radiation resistance occurring in the S phase or in G 2 /M phase arrest (16,17). Particularly in the G 2 phase, longer duration of the cell cycle arrest results in more frequent occurrence of potentially lethal DNA damage repair.…”
Section: Discussionmentioning
confidence: 99%